Digital color management : encoding solutions - Giorgianni, Edward J., 1944- (J. Wiley, 2008)
All successful imaging systems employ some form of color management for previewing, controlling and adjusting color throughout the image-production process. Todays increasingly complex systems pose challenging problems: they must support numerous devices and media having disparate color properties, and they also must provide for the interchange of images among dissimilar systems. In this book, the authors address and solve these problems using innovative methods of representing color in the digital domain. The second edition of this popular book explains the capabilities and limitations of ex.